SrIr9In18 – A Structurally Complex Intermetallic Compound with Sr@Ir4In12, Ir@In8 and Ir@In9 Building Units. Issue 13 (31st October 2019) - Heying, Birgit; Hoffmann, Rolf‐Dieter; Kösters, Jutta; Pöttgen, Rainer
Abstract : Single crystals of SrIr9 In18 were obtained by induction melting of the elements in a glassy carbon crucible followed by annealing at 1070 K. SrIr9 In18 was structurally characterized by X‐ray powder and single crystal diffraction: P 4 m 2, a = 811.21(5), c = 854.49(5) pm, wR 2 = 0.0511, 1223 F 2 values, and 46 variables. The structure is of a new type. The basic building units are Ir@In8 (distorted square‐prismatic, square anti ‐prismatic and bicapped trigonal prismatic coordination) and Ir@In9 (distorted trigonal prismatic coordination) polyhedra, which condense to a three‐dimensional network, which leaves large cavities for the strontium cations, which are coordinated to four iridium and twelve indium atoms. The [Ir9 In18 ] 2– polyanionic network is stabilized through Ir–In (267–290 pm) and In–In (302–354 pm) bonding. Abstract :